Cross-sectional study of glycemic control among adults with type 2 diabetes - Amarasekara,A.T.D.A. (Wiley-Blackwell, 2015)
© 2014 Wiley Publishing Asia Pty Ltd. Type 2 diabetes mellitus is a chronic condition, a global concern, and a serious issue in Sri Lanka, where there is little data regarding the influence of dietary control, exercise, and adherence to medication behaviors among adults diabetes. In this cross-sectional, descriptive study, we identified current factors influencing glycemic control and glycemic control behavior among adults with diabetes. A total of 230 people attending diabetes clinics in a tertiary hospital and a primary care institute were administered the self-report Diabetes Information Form, assessing their socioeconomic and medical information and glycemic control behaviors. Data were analyzed by frequency distribution, percentages, mean scores, and standard deviation. The results indicated that most participants had not achieved the recommended fasting blood glucose level (<126mg/dL). Although dietary control was practised by 72%, regular exercise was not practised by 85%, and while 77% reported adhering to regular medication, they still had poor glycemic control. The findings highlight the need for health professionals to adopt new strategies for diabetes education to overcome issues related to misconceptions and barriers in providing diabetes care in Sri Lanka.